2021
DOI: 10.1099/mgen.0.000477
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics of Mycobacterium africanum reveals a new lineage and a complex evolutionary history

Abstract: Human tuberculosis (TB) is caused by members of the Mycobacterium tuberculosis complex (MTBC). The MTBC comprises several human-adapted lineages known as M. tuberculosis sensu stricto, as well as two lineages (L5 and L6) traditionally referred to as Mycobacterium africanum . Strains of L5 and L6 are largely limited to West Africa for reas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
168
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(183 citation statements)
references
References 61 publications
15
168
0
Order By: Relevance
“…However, L6 strains are found in limited geographical regions and represent only a small minority of all tuberculosis infections (23); however, early clinical trials may need to avoid the regions where L6 strains are prevalent. There are additional lineages we have not yet tested, including L7, L8, and L9, although L7 is also rare and is restricted to Ethiopia, and both L8 and L9 have been reported from very few individual patients (25,29). It would also be helpful to examine a much broader set of clinical isolates and more drug-resistant strains, especially those in lineages L2, and L4, which are more diverse, more virulent, and more likely to become drug resistant (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, L6 strains are found in limited geographical regions and represent only a small minority of all tuberculosis infections (23); however, early clinical trials may need to avoid the regions where L6 strains are prevalent. There are additional lineages we have not yet tested, including L7, L8, and L9, although L7 is also rare and is restricted to Ethiopia, and both L8 and L9 have been reported from very few individual patients (25,29). It would also be helpful to examine a much broader set of clinical isolates and more drug-resistant strains, especially those in lineages L2, and L4, which are more diverse, more virulent, and more likely to become drug resistant (30).…”
Section: Discussionmentioning
confidence: 99%
“…This gene was studied in the Beijing lineage as a possible cause of a major number of SNPs related to resistance 43 . It has been observed that L6 has a higher variability in its genome in comparison to L5, which could be related to a higher mutation rate 44 , 45 . MutT2 is involved in DNA repair, therefore the mutation detected in the mutT2 promoter could increase the polymorphisms in L6 strains 46 .…”
Section: Discussionmentioning
confidence: 99%
“…One genome was from a Benin isolate [PcbL5Ben; sequenced in this study, National Center for Biotechnology Information (NCBI) accession PRJNA641267], one from an isolate from The Gambia (PcbL5Gam, WBB1453_11-00429-1) [1] and one from Nigeria (PcbL5Nig, WBB1454_IB091-1) [1]. These genomes also represent disparate parts of L5's diversity, representing a broad range of L5 sub-lineages, as recently defined [6]. The previously published reference/complete genomes H37Rv (L4) (NC_000962.3) [39,40,49], L6 (GM041182, GenBank accession: FR878060.1, GCF_0001593225.1_ ASM159322v1) [50] and M. bovis (AF2122/97, accession: LT708304.1) [51] were also included.…”
Section: Genomesmentioning
confidence: 99%